Pengaruh Media Disc triage assessment Terhadap triage skills pada Australasian Triage Scale (ATS) - Rosida, Nikma Alfi; Saputro, Sutiyo Dani; Rahmad, Muhamad Nur; Budiman, Amin Aji (LPPM Universitas Harapan Bangsa, 2023)
Triage Australasian Triage Scale is a tool used by triage nurses in emergency departments to assess patient severity and provide priority services based on the severity of the patient's condition. This study aims to evaluate the effect of using learning tools in the form of visual aids in the form of Disc triage assessment as learning media in increasing understanding and accuracy in determining triage by students using ATS triage. The research method used is quasi-experimental. The research sample was 44 students with educational treatment using Disc triage assessment media. Measurements were carried out using a pre-test and post-test 1 month later which included accuracy in determining patient priorities using ATS. Data analysis was performed using the Wilcoxon test. Based on bivariate analysis, the p value is 0.000 (<0.05), which means that there is an influence of the Media Disc triage assessment on the Australasian Triage Scale (ATS) triage skills.